Anesthesia and postoperative analgesia during unilateral lower-extremity fracture surgeries using multiple injections through catheters beside the lumbar plexus or sciatic nerve - Zhang X; Zhou Y; Chen L; Wang Q; Ni J; Liu L; Hu C; Xu X (Dove Medical Press, 2013)
Xuezheng Zhang,1 Ying Zhou,1 Limei Chen,1 Quanguang Wang,1 Jianwu Ni,1 Le Liu,1 Chenggang Hu,2 Xuzhong Xu11Department of Anesthesiology, First Affiliated Hospital of Wenzhou Medical College, Wenzhou, Zhejiang, People’s Republic of China; 2Department of Anesthesia, Pomerado Hospital, Poway, CA, USAObjective: To compare the clinical effects of anesthesia and postoperative analgesia for patients with unilateral lower-extremity fracture between multiple injections through catheters beside the lumbar plexus or sciatic nerve and continuous epidural analgesia.Methods: Seventy patients with unilateral lower-extremity fracture scheduled for internal fixation were randomly divided into group N (n = 35) and group E (n = 35). Patients in group N received combined lumbar plexus and sciatic nerve block, then a catheter was inserted into the psoas compartment or beside the sciatic nerve, according to the surgical site, and 25 mL 0.375% ropivacaine was injected into patients in group N through the peripheral nerve catheter 12 hours after operation. Patients in group E received combined spinal and epidural anesthesia, and when the operation was complete kept the epidural catheter and received patient-controlled epidural analgesia with an analgesia pump.Results: The visual analog scores of patients at each time point in the two groups showed no significant difference (P > 0.05). Mean arterial pressure at 30 minutes after anesthesia and 4 hours postoperation in group E decreased significantly and was significantly lower than group N (P < 0.01). Group E had significantly higher rate of urinary retention than group N (P < 0.05), and the time of first food intake of patients in group N was significantly shorter than in group E (P < 0.001).Conclusion: For patients with unilateral lower-extremity fracture receiving internal fixation, multiple injections through catheters beside the lumbar plexus or sciatic nerve can provide adequate postoperative analgesia, with very few adverse effects.Keywords: lumbar plexus, sciatic nerve, catheterization, lower extremity, analgesia